Major Histocompatibility Complex Class II Expression by Intrinsic Renal Cells Is Required for Crescentic Glomerulonephritis - Li, Shuo (The Rockefeller University Press, 1998)
The requirement for major histocompatibility complex class II (MHC II) to initiate immune renal injury was studied in a murine model of CD4(+) T cell–dependent crescentic glomerulonephritis (GN). C57BL/6 (MHC II(+/+) ) mice developed crescentic GN with glomerular CD4(+) T cell infiltration and renal injury, in response to a nephritogenic antigen (sheep globulin) planted on their glomerular basement membrane. MHC II–deficient C57BL/6 mice (MHC II(−/−) ) did not develop crescentic GN, CD4(+) T cell infiltration, or injury, indicating that this form of immune glomerular injury is MHC II dependent. The requirement for MHC II expression by intrinsic renal cells was studied in chimeric mice, which expressed MHC II on bone marrow–derived cells and in the thymus, but not in the kidneys. These chimeric mice had normal T and B cell populations and MHC II expression in their spleens and lymph nodes and developed an immune response to systemically and cutaneously administered sheep globulin. However, they did not develop crescentic GN, CD4(+) T cell infiltration, or renal injury in response to the sheep globulin planted in their glomeruli. These studies demonstrate that interaction of CD4(+) T cells with intrinsic renal cells expressing MHC II is required for development of cell-mediated immune renal injury.